Relationship between Pancreas Exocrine Insufficiency and Cardiac Autonomic Neuropathy in Patients with Type 2 Diabetes Mellitus - Abidin Sayiner, Zeynel; Uyar, Nida; Yıldırım, Abdullah Emre (Turkish Journal of Gastroenterology, 2021)
Background: The exocrine function of the pancreas is controlled by the autonomic nervous system (ANS), and autonomic neuropathy is a common and serious complication of diabetes. There are many factors contributing to the development of autonomic neuropathy in diabetic patients. Cardiovascular tests have been developed to evaluate the function of the ANS. This study investigated the relationship between cardiovascular autonomic neuropathy (CAN) and pancreas exocrine insufficiency (PEI) in diabetic patients. Methods: This study evaluated 110 individuals with type 2 diabetes mellitus (T2DM) and 40 healthy volunteers. Autonomous neuropathy tests were utilized to diagnose patients, and Ewing and Clarke’s criteria were employed to assess the severity of autonomous dysfunction. Stool samples were also collected from patients to measure fecal elastase-1 (FE-1). Results: A 65.5% incidence of PEI was observed in DM patients. There was no significant correlation among the duration of disease, C-peptide, HbA1c, and PEI, respectively (P = .782, P = .521, P = .580). However, a significant difference between DM patients and controls in terms of cardiac dysautonomia (P = .001) was seen. Moreover, a statistically significant correlation between the degree of cardiac dysautonomia and FE-1 level was observed within the patient group (P =.001). Conclusion: It is possible that the disruption of exocrine hormone secretion in the pancreas due to the impairment of enteropancreatic reflexes is secondary to diabetic autonomic neuropathy and resulting in PEI. This study also showed that autonomic neuropathy might develop and cause PEI in diabetic patients without known added confounding factors.